Can new technologies in agriculture save the forests? - Angelsen, A.; Kaimowitz, D. (1999)
This paper addresses under what circumstances technological change in agriculture is likely to increase deforestation and when it will decrease it. It identifies four sets of variables that influence these outcomes: the type of technological change involved, the farmers' socio-economic profile, the conditions in the relevant product and factor markets, and the agro-ecological contexts in which the technologies are introduced. Labor intensive technologies tend to reduce deforestation, as do technologies that lead to large price decreases for the output produced. Capital intensive technologies associated with mechanized agriculture or cattle ranching are much more likely to increase deforestation.